2004
DOI: 10.1021/ef034067u
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Applications of Biomass Fast Pyrolysis Oil

Abstract: Fast pyrolysis of biomass is one of the most recent renewable energy processes to have been introduced. It offers the advantages of a liquid product, bio-oil that can be readily stored and transported. Bio-oil is a renewable liquid fuel and can also be used for production of chemicals. Fast pyrolysis has now achieved a commercial success for production of chemicals and is being actively developed for producing liquid fuels. Bio-oils have been successfully tested in engines, turbines, and boilers, and have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,831
3
43

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,614 publications
(1,904 citation statements)
references
References 50 publications
27
1,831
3
43
Order By: Relevance
“…It can be seen in Table 1 that SP almost has twice as much of ash content than that of CP, which is mainly due to the high alkali metal content in the feedstock (Kay, 1991). Previous studies (Liden et al, 1998;Czernik and Bridgwater, 2004) showed that sodium, potassium, magnesium and silicate in ash significantly affect pyrolysis degradation of biomass material, while potassium, sodium, calcium and magnesium are the main components influencing the combustion process. According to Kay (1991), the content of potassium, sodium, calcium and magnesium of SP is higher than that of CP.…”
Section: Combustion Characteristicsmentioning
confidence: 95%
“…It can be seen in Table 1 that SP almost has twice as much of ash content than that of CP, which is mainly due to the high alkali metal content in the feedstock (Kay, 1991). Previous studies (Liden et al, 1998;Czernik and Bridgwater, 2004) showed that sodium, potassium, magnesium and silicate in ash significantly affect pyrolysis degradation of biomass material, while potassium, sodium, calcium and magnesium are the main components influencing the combustion process. According to Kay (1991), the content of potassium, sodium, calcium and magnesium of SP is higher than that of CP.…”
Section: Combustion Characteristicsmentioning
confidence: 95%
“…[31][32][33] Nevertheless, they have several undesirable features such as high oxygen content, low heat content, high viscosity at low temperature, and chemical instability [31][32][33] that impede their use as quality transportation fuels. To overcome this limitation, studies have been taken to upgrade the bio-oils to high quality fuels.…”
Section: Bio-oil and Bio-syngasmentioning
confidence: 99%
“…Today, bio-oil can substitute fuel oil or diesel in many static applications including boilers, furnaces, engines and turbines used for electricity generation. Additionally, it can be upgraded to transportation fuels [7] and even to chemicals with added value.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the presence of water has both positive and negative effects on the bio-oil properties [5,8]. It improves bio-oil flow characteristics, which is beneficial for combustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation